Efektivitas Mangrove di Pesisir Kabupaten Majene dalam Meredam Energi Gelombang Tsunami - Yusman (Universitas Sulawesi Barat, 2022)
The Majene Coast is a seismically active area that stretches along the coastline of West Sulawesi, making it prone to earthquakes and tsunamis. Mangrove vegetation is the right protection because it is environmentally friendly and sustainable. Mangrove forest with a thickness of about 200 meters towards the sea with a density of 60 stems and a diameter of 15 cm can reduce the ferocity of tsunami wave energy by up to 50%. Mangrove forests with a thickness of 600 m to 1 km are able to absorb around 80% of tsunami waves up to a run-up height of 10 m. The coast of Majene Regency currently covered by mangroves is 11.23 km or 9.61% of the total length of 116.83 km and not covered by mangroves is 105.6 km or 90.49%. The total area of ​​mangroves on the coast of Majene Regency is 701,702,378 m2. The aim of this research is to determine the effectiveness of mangrove density on the coast of Majene Regency at this time in reducing tsunami wave energy. The method used is the observation method using Landsat 8 satellite imagery, as well as data processing using ArcMap 10.4.1 and Microsoft Excel 2007. From the results of the study, mangroves with a length of more than 200 m towards the sea cover an area of ​​17,993,420 m2 or 2% of the total the area of ​​the existing mangroves, while the rest is less than 200 m to the sea, covering an area of ​​683,708,958 m2 or 98%. This indicates that the current mangroves on the coast of Majene Regency are still less effective in reducing tsunami wave energy.